Sex differences in the therapeutic efficacy of oxytocin receptor signaling in a rat model of vascular cognitive impairment. (1st February 2022) - Counts, Scott E.; Beck, John S; McKay, Erin C.
Abstract: Background: We recently demonstrated a de novo upregulation of the oxytocin receptor (OXTR) in astrocytes located in the peri‐infarct region of both male and female subjects who died with vascular dementia (multi‐infarct subtype). OXTR activation has been linked to antioxidant, anti‐inflammatory, and angiogenic signaling, suggesting that OXTR upregulation is a novel protective target for vascular contributions to cognitive impairment and dementia (VCID) and perhaps stroke more generally. To test this hypothesis, we modeled OXTR upregulation in a novel rat model for VCID. Method: Four month‐old spontaneously hypertensive, stroke prone rats ( n = 68; 38 male, 30 female) were randomized to receive frontal cortical injections of adeno‐associated virus (AAV, serotype 6) bearing either OXTR or green fluorescent protein (GFP) cDNA under control of the astroglial‐specific GFAP promoter ( n = 34/group), followed by randomization to receive injections of the vasoconstrictor endothelin‐1 (ET‐1) or saline vehicle in the same frontal cortical surgical site (n = 17/group, balanced for sex). Following behavioral testing, rats were analyzed postmortem for infarction lesion size and cerebrovascular pathology including white matter damage. Current studies are investigating several mechanistic indices including markers for cell death, inflammation, and oxidative stress. Result: No significant differences were observed among the groups in the open field test or the Barnes maze. By contrast, rats receiving AAV‐OXTR and ET‐1 spent approximately twice as much time exploring novel versus familiar objects in the novel object recognition task compared to rats receiving AAV‐GFP and ET‐1 ( p = 0.039). Further analysis revealed that this preservation of object recognition memory was limited to the male animals ( p = 0.032), with no differences in the females ( p = 0.847). Postmortem histological analysis revealed a significant ∼50% reduction in infarct size in OXTR/ET‐1 compared to GFP/ET‐1 rats ( p = 0.022), which was driven by the male animals ( p = 0.014) when compared to the female animals ( p = 0.527). White matter density among the groups was equivalent ( p = 0.631). Conclusion: These data support the concept that targeting the OXTR may have a disease‐modifying benefit for VCID in males.